2024
DOI: 10.1039/d3fb00130j
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Brazilian berries in developing innovative, healthy, and sustainable food products

Nayara Macêdo Peixoto Araujo,
Paulo Berni,
Lais Ramalho Zandoná
et al.

Abstract: There is a considerable diversity of Brazilian berries, purple in color, and potentially rich in anthocyanins, which are an unexplored source of new foods, products, extracts, and compounds of economic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 132 publications
0
1
0
Order By: Relevance
“…Previous studies have found a direct correlation between health and a fruit-rich diet [ [7] , [8] , [9] ]. Certain fruits may be associated with an observable decrease in the risk of diseases potentially caused by oxidative stress, as found with the use of Andean blueberry or “ mortiño " [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found a direct correlation between health and a fruit-rich diet [ [7] , [8] , [9] ]. Certain fruits may be associated with an observable decrease in the risk of diseases potentially caused by oxidative stress, as found with the use of Andean blueberry or “ mortiño " [ 10 ].…”
Section: Introductionmentioning
confidence: 99%